Attrition in Long-Term Nutrition Research Studies: A Commentary by the European Society for Pediatric Gastroenterology, Hepatology, and Nutrition Early Nutrition Research Working Group. Issue 1 (January 2016) - Fewtrell, Mary S.; Domellöf, Magnus; Hojsak, Iva; Hulst, Jessie M.; Kennedy, Kathy; Koletzko, Berthold; Mihatsh, Walter; Stijnen, Theo
Abstract : ABSTRACT: Long-term follow-up of randomised trials and observational studies provide the best evidence presently available to assess long-term effects of nutrition, and such studies are an important component in determining optimal infant feeding practices. Attrition is, however, an almost inevitable occurrence with increasing age at follow-up. There is a common assumption that studies with <80% follow-up rates are invalid or flawed, and this criticism seems to be more frequently applied to follow-up studies involving randomised trials than observational studies. In this article, we explore the basis and evidence for this "80% rule" and discuss the need for greater consensus and clear guidelines for analysing and reporting results in this specific situation.